An Integrated Food, Energy, and Water Nexus, Human Well-Being, and Resilience (FEW-WISE) Framework: New Mexico - Yadav, Kamini; Geli, Hatim M. E.; Cibils, Andres F.; Hayes, Michael; Fernald, Alexander; Peach, James; Sawalhah, Mohammed N.; Tidwell, Vincent C.; Johnson, Lindsay E.; Zaied, Ashraf J.; Gedefaw, Melakeneh G. (Frontiers in Environmental Science, 2021)
Interconnected food, energy, and water (FEW) nexus system experiences many challenges to maintain human wellbeing (HWB) and resilience, especially in arid regions like New Mexico (NM), USA. Insufficient FEW resources, irregular economic growth due to fluctuations in crude oil and natural gas prices, inequitable education and employment, and climate change are among the challenges that also acts as drivers of FEW nexus. Enhancing the resilience of such coupled natural-human systems in response to these drivers (e.g., climate change and socioeconomic stresses) depends on efficient use of resources, understanding the interlinkages across FEW components, and adopting adaptable alternative management plans. The goal of this study was to develop an integrated FEW-HWB framework to enhance resilience of these systems referred to here in as FEW-WISE. Therefore, an integrated Food, Energy, Water, Well-beIng, and reSiliEnce framework (i.e., FEW-WISE) was developed for quantitative assessment of FEW systems’ relationships, identification of important external drivers, predictive modeling, and threshold-based resilience monitoring determined by FEW-HWB performance metrics (i.e., indices). The integrated FEW-WISE framework evaluates and predicts the behavior of FEW systems in response to environmental and socioeconomic shocks. System-based dynamic modeling of FEW-HWB relationships along with the performance metrics have the potential to serve as a measure of resilience that can inform decision-making processes. In conclusion, the derived resilience metrics can be used to develop alternative scenario-based management strategies to enhance resilience and sustainability of ecological and socioeconomic wellbeing of vulnerable regions like New Mexico.